Implementasi Panel Surya Untuk Medukung Aktivitas Pelayanan Administrasi Pada Kantor Desa Borisallo Kecamatan Parangloe Kabupaten Gowa - Masa, M. Anas; Basalamah, Abdullah; Altim, Muhammad Zainal; Syamsir, Syamsir (Journal Of Human And Education (JAHE), 2024)
The electricity condition of Borisallo Village, Parangloe District, Gowa Regency in South Sulawesi in the dry season has not been completely stable, which has disrupted administrative service activities at the village office. In Borisallo Village, based on its topology, the exposure to sunlight is quite good throughout the year and has a large area for the placement of solar panels, which can be optimized to support the electrical activities of the village office. The purpose of this PKM activity is to implement solar panels to support efficient, stable, and sustainable administrative service activities, as well as to increase the understanding and skills of village officials related to solar panel technology and increase public awareness of the importance of renewable energy. Solar panels implemented in the Office. Borisallo Village can function well to run electronic equipment such as computers or laptops, printers, LED lights, small fans, as well as mobile phone battery charging with a usage time of about 4 hours under normal conditions. Then, the level of understanding and proficiency of village officials who participated in the training increased significantly with an average increase 57.34%.